Attitudes Towards Suicide among People with Eating Disorders - Toleikytė, Uršulė (Socialinė teorija, empirija, politika ir praktika, 2021)
Clients of social workers have elevated suicide risks. One of those types of clients are people with eating disorders. Suicidality is associated with attitudes towards suicide. Although the suicidality of people with eating disorders is well-studied, their attitudes towards suicide have received less attention. The object of this research is to study the attitudes among people with eating disorders – 126 participants took place in this research: 63 people with eating disorders (anorexia nervosa, bulimia nervosa, binge eating disorder, other eating disorders) and 63 people without eating disorders. All the participants with eating disorders at the time of the research were receiving treatment at the Center for Eating Disorders (VšĮ Vilnius Mental Health center). The majority of participants were women (92%), with an average age of 25 years. All the respondents filled in an Attitudes towards suicide questionnaire (ATTS) and its supplement. The results showed that participants with eating disorders perceived suicide as less predictable and associated it with loneliness more than participants without eating disorders. Attitudes of people with anorexia nervosa and with bulimia nervosa towards suicide did not differ significantly. Participants with anorexia nervosa perceived suicide as less predictable, showed more nonintrusive attitudes towards suicide and associated it with loneliness more than participants without eating disorders. Attitudes towards suicide among people with bulimia nervosa and people without eating disorders did not differ significantly. The results could be explained by considering the characteristics of people with eating disorders and the methodology of this research. Recommendations for social work practice were formed based on the findings.